Topics

A) 100 |

B) 80 |

C) 86 |

D) 90 |

Correct Answer:

D) 90 |

Description for Correct answer:

Let first number = x

and second number = y

According to the question.

x - y = 18 ...(i)

and 3x - 4y = 18 ...(ii)

On multiplying Eq. (i) by 3 and then subtracting Eq. (ii) from it, we get

3x - 3y = 54

3x - 4y = 18

y = 36

On putting the value of y in Eq. (i), we get

x = 18 + y = 18 + 36 => x = 54

Therefore, Required sum = x + y = 54+ 36 = 90

Let first number = x

and second number = y

According to the question.

x - y = 18 ...(i)

and 3x - 4y = 18 ...(ii)

On multiplying Eq. (i) by 3 and then subtracting Eq. (ii) from it, we get

3x - 3y = 54

3x - 4y = 18

y = 36

On putting the value of y in Eq. (i), we get

x = 18 + y = 18 + 36 => x = 54

Therefore, Required sum = x + y = 54+ 36 = 90

Part of solved Word problems questions and answers : >> Aptitude >> Word problems

Comments

Similar Questions